Efficacy of Anakinra in Refractory Adult-Onset Still's Disease: Multicenter Study of 41 Patients and Literature Review. Issue 39 (September 2015) - Ortiz-Sanjuán, Francisco; Blanco, Ricardo; Riancho-Zarrabeitia, Leyre; Castañeda, Santos; Olivé, Alejandro; Riveros, Anne; Velloso-Feijoo, María.L.; Narváez, Javier; Jiménez-Moleón, Inmaculada; Maiz-Alonso, Olga; Ordóñez, Carmen; Bernal, José A.; et al.
Abstract : Abstract: Adult-onset Still's disease (AOSD) is often refractory to standard therapy. Anakinra (ANK), an interleukin-1 receptor antagonist, has demonstrated efficacy in single cases and small series of AOSD. We assessed the efficacy of ANK in a series of AOSD patients. Multicenter retrospective open-label study. ANK was used due to lack of efficacy to standard synthetic immunosuppressive drugs and in some cases also to at least 1 biologic agent. Forty-one patients (26 women/15 men) were recruited. They had a mean age of 34.4 ± 14 years and a median [interquartile range (IQR)] AOSD duration of 3.5 [2–6] years before ANK onset. At that time the most common clinical features were joint manifestations 87.8%, fever 78%, and cutaneous rash 58.5%. ANK yielded rapid and maintained clinical and laboratory improvement. After 1 year of therapy, the frequency of joint and cutaneous manifestations had decreased to 41.5% and to 7.3% respectively, fever from 78% to 14.6%, anemia from 56.1% to 9.8%, and lymphadenopathy from 26.8% to 4.9%. A dramatic improvement of laboratory parameters was also achieved. The median [IQR] prednisone dose was also reduced from 20 [11.3–47.5] mg/day at ANK onset to 5 [0–10] at 12 months. After a median [IQR] follow-up of 16 [5–50] months, the most important side effects were cutaneous manifestations (n = 8), mild leukopenia (n = 3), myopathy (n = 1), and infections (n = 5). ANK is associated with rapid and maintained clinical and laboratory improvement, even in nonresponders to other biologic agents. However, joint manifestations are more refractory than the systemic manifestations.